The unheimlich and the contemporary aesthetic-political paradigm: methodology and thoughts on the inhuman implications of our everyday life: The unheimlich and the contemporary aesthetic-political paradigm: methodology and thoughts on the inhuman implications of our everyday life (Simbiótica. Revista Eletrônica, 2024)
This text aims to investigate the unheimlich, feeling present in Freud's 1919 text, using the interpretation made by Lacan to develop his object a to defend the aspect present in this investigation in a possible method for psychoanalysis in the face of suffering, anguish and malaise in situations of indetermination. Within conceiving the unheimlich under Lacanian lenses, there is a clinical method that allows a dialectical movement in psychoanalysis to deal with the creation of a necessary grammar for an experience of subjective suffering.
Keywords: uncanny; Lacan; Freud; anguish